(untitled) - Rother, Tom (New York, NY, 2017)
This book presents the Green’s function formalism in a basic way and demonstrates its usefulness for applications to several well-known problems in classical physics which are usually solved not by this formalism but other approaches. The book bridges the gap between applications of the Green’s function formalism in quantum physics and classical physics. This book is written as an introduction for graduate students and researchers who want to become more familiar with the Green’s function formalism.
Keywords: Mathematical physics,Toán lý